2016
DOI: 10.1007/s13201-016-0419-y
|View full text |Cite
|
Sign up to set email alerts
|

Climate change impact on soil erosion in the Mandakini River Basin, North India

Abstract: Correct estimation of soil loss at catchment level helps the land and water resources planners to identify priority areas for soil conservation measures. Soil erosion is one of the major hazards affected by the climate change, particularly the increasing intensity of rainfall resulted in increasing erosion, apart from other factors like landuse change. Changes in climate have an adverse effect with increasing rainfall. It has caused increasing concern for modeling the future rainfall and projecting future soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 29 publications
2
20
0
3
Order By: Relevance
“…Studies in Swiss Alps have revealed that the increase in the overall magnitude of debris flows is expected with the increase in extreme precipitation events, which can be attributed to climate change (Stoffel et al 2014). Likewise, the studies have shown that increasing rainfall due to climate change will also increase soil erosion in the Himalayas (Khare et al 2016). Record shows that there has been series of landslide, flood and avalanche disaster Table 6 Projected change in annual precipitation for future periods compared to baseline under three RCPs As far as the casualties and damages due to landslide are considered, it is widespread in the basin.…”
Section: Climate Change Implication In Geodisastersmentioning
confidence: 99%
“…Studies in Swiss Alps have revealed that the increase in the overall magnitude of debris flows is expected with the increase in extreme precipitation events, which can be attributed to climate change (Stoffel et al 2014). Likewise, the studies have shown that increasing rainfall due to climate change will also increase soil erosion in the Himalayas (Khare et al 2016). Record shows that there has been series of landslide, flood and avalanche disaster Table 6 Projected change in annual precipitation for future periods compared to baseline under three RCPs As far as the casualties and damages due to landslide are considered, it is widespread in the basin.…”
Section: Climate Change Implication In Geodisastersmentioning
confidence: 99%
“…Outro dado pertinente da pesquisa é que os autores estimam que a substituição de florestas por lavouras poderá representar 26% do aumento da erosão do solo. Khare et al (2017) realizaram um estudo para estimar o valor R e a perda de solos por erosão para o período de 2020-2080, para a bacia hidrográfica do rio Mandakini, localizada também na Índia. O valor de solo perdido praticamente deve dobrar no período avaliado, com a porcentagem de mudança nas décadas de 2020 e 2080 sendo maior do que em 2050, resultado que difere de Pal et al (2021).…”
Section: Methodsunclassified
“…Plangoen e Udmale (2017) estimaram os impactos das mudanças climáticas na erosividade da chuva para a bacia hidrográfica de Huai Luang, Tailândia, utilizando modelos climáticos multivariados. A avaliação comparou os valores da erosividade da chuva de uma linha base de 1982-2005 com Mondal et al (2016b) e Khare et al (2017). Giang et al (2017) calcularam os valores de erosão do solo para a bacia hidrográfica transnacional do Rio Alto Ca do Laos, Vietnã, que possui aproximadamente 22.800 km².…”
Section: Methodsunclassified
“…Ekspansi lahan pertanian ke padang rumput dan semak belukar juga menjadi penyebab utama erosi berat di DAS Rib, Ethiopia (Moges et al, 2017). Selain diakibatkan oleh perubahan penutupan lahan, erosi sebagai penyebab degradasi juga diakibatkan oleh adanya perubahan iklim dan perubahan intensitas hujan yang akan berdampak pada peningkatan tingkat erosi lahan (Khare et al, 2017 (Khare et al, 2017). Oleh karena itu, tujuan penelitian ini adalah untuk mengidentifikasi sebaran lahan terdegradasi di DAS Brantas sebagai upaya dalam melakukan rehabilitasi hutan dan lahan secara tepat sasaran.…”
Section: Pendahuluanunclassified